Standards probatórios em crimes sexuais - Barbosa, Deise Araújo (2020)
Standards of proof, as a proposal to rationalize the valuation of criminal evidence, constitute an instrument for objectifying the judicial decision and establishing minimum criteria for confirming the accusatory factual hypothesis. In sexual assault cases, it has peculiarities resulting from the hidden condition in which the act is usually performed, so that the jurisprudence accepts the victim's narrative as the main means of proving the crime, when coherent and harmonized with other evidence. However, because it is often the only direct evidence, the victim´s case report require a more accurate examination, in order to avoid, on the one hand, subjective judicial analyzes and contamination of socio-moral factors and, on the other, to check such proof proves absolute validity. Therefore, the present work aims to analyze the standards of proofs in sexual offences, as well as to propose parameters for the evaluation of evidence in theese criminal species. In the first part, the notion of an evidentiary standard is presented, as well as its outlines in the criminal sphere. Second, the institute's particularities in the area of sexual crimes are analyzed based on the minimum probative decision standards adopted by the doctrine and jurisprudence. The third part intents to study of the victim's report, exposing the human’s memory questions, such as false memories, false identification and suggestibility for parental alienation. Finally, ways of better assessing the victim's ability to testify were exposed, besides more effective methods of collecting his testimony and valuation parameters on the report provided, on the principles of credibility and reliability, in order to comply with such species criminal standard of criminal evidence. The methodology used was of qualitative nature, with indirect investigation, through bibliographic research, with exploratory, descriptive, explanatory and propositional way.